BODIES THAT TALK, MOTHERS WHO SUFFER: SOCIAL STIGMA AND PSYCHOLOGICAL SUFFERING IN ATYPICAL MOTHERHOOD - Dornelles da Silva, Carla; Luci Freire de Duran, Maria (Revista Gênero e Interdisciplinaridade, 2025)
This article aims to analyze the processes of stigmatization, prejudice, and social recognition experienced by mothers of atypical children, as well as to understand the processes of subjectivation that, in contemporary times, shape the ways in which these individuals experience, produce, and recognize themselves as individuals in both the fields of education and health. The central problem will be to understand how experiences of stigma and social exclusion impact the construction of these mothers’ identities, influencing their life trajectories, their social relationships, and their care practices. The guiding question that guides this work is: How do processes of stigmatization and social recognition influence the subjectivation of mothers of atypical children, and how can psychosocial actions promote the recognition and reframing of these experiences? To theoretically support the study, we will use authors who address the dynamics of stigma, the formation of subjectivity, and the role of the social environment in the constitution of the subject, such as: Goffman, E. (2020), López, M. A., & Silva, M. A. (2021), Silva, C. M., & Oliveira, R. (2022), Mendes, A. C., & Santos, L. (2020), Branco, A. M., & Pereira, M. (2023), among others. The methodology adopted is a qualitative, integrative approach to groups of mothers of atypical children. It highlights the importance of spaces for listening, expression, and resignification of stigma experiences, promoting social recognition and strengthening resilience strategies. Thus, we seek to understand the emotions and meanings attributed by mothers to their experiences. The results are expected to contribute to a broader understanding of the dynamics of stigmatization and subjectivation, providing support for educational and health practices sensitive to the specific needs of these mothers and their children. Furthermore, the aim is to promote reflection on the role of the social environment and ethos in the formation of identities, proposing intervention strategies that foster social recognition, inclusion, and integral human development. Thus, the study seeks to contribute to the advancement of knowledge at the interface between education, health, and social sciences, promoting a more humane and inclusive approach to caring for families of atypical children.